Fighting for common ground : how we can fix the stalemate in Congress - Snowe, Olympia J. (Olympia Jean), 1947- (New York, NY : Weinstein Books, 2013)
In this timely call to action, Snowe explores the roots of her belief in principled policy-making and bipartisan compromise. A leading moderate with a reputation for crossing the aisle, Snowe proposes solutions for bridging the partisan divide in Washington.
Includes index.
Keywords: Snowe, Olympia J. -- 1947-; United States. -- Congress. -- Senate -- Biography; Legislators -- United States -- Biography; Women legislators -- United States -- Biography; United States -- Politics and government -- 20th century; United States -- Politics and government -- 21st century